Adverse effects of technical fouls in elite basketball performance - Miguel-Ángel Gómez; Simcha Avugos; Enrique Ortega; Michael Bar-Eli (Termedia Publishing House, 2019)
This study examined the temporal effects of technical fouls on the performance of the fouling and opposing teams in elite basketball games. A sample of 80 technical fouls was collected from 65 international games. The fouls were charged either to players on court or to the bench players/coaching staff. Performance measures considered were the points scored (during 1, 3, and 5 ball possessions), fouls received, violations, and turnovers during 5 ball possessions before and after a technical foul was called. Data were also obtained on several contextual variables. The results showed that the opposing team scored slightly more points compared to the fouling team during 1 ball possession before and after a foul was charged to the coach/bench personnel (F=5.934; p=0.019; ES=0.11). The results also showed that both types of technical fouls are generally positive for the opposing team (mid-term effects) and for the fouling team only during the short-term performance (points scored after 1 ball possession). Furthermore, significant differences between teams were found when comparing the fouls received, with the opposing team receiving more fouls after both types of technical fouls (F=5.364; p